Drop-casting and printing of carbon nanotube field-effect-transistor (CNTFET) and its behavior under cryogenic and high vacuum condition - Cai, Fei (2010)
Effective separation of semiconducting and metallic species in Single Wall Carbon Nanotube (SWCNT) is crucial to explore applications of carbon nanotube (CNT). A wet separation method developed by Zhao et al. in 2009 [1] was employed to achieve good separation. Fabrication methods of carbon nanotube field effect transistor (CNTFET) including simple drop-casting and inkjet printing were explored. The drop-casted device with the best performance has high ON/OFF ratio (approximately 1.17×106) and high mobility (approximately 9.857 cm2V-1S-1). However, due to the unsatisfactory purity of Dimethylformamide (DMF), the performance of printed devices is not as good as expected, with an ON/OFF ratio about 1.03×104 and mobility about 0.636 cm2V-1S-1. In addition, drop-casted CNTFET devices were carried out temperature study from room temperature down to 15 K. The gate hysteresis and output current of the CNTFET devices simultaneously reduce with decrease in temperature, suggesting that this phenomenon is likely due to removal of oxygen or moisture surrounding SWNTs. As knowing that SWNT in ambient with surrounding of oxygen and moisture results in p-doping effect to SWNT, Removal of oxygen or moisture surrounding SWNTs in vacuum and low temperature condition lead to reduction in the output current. Furthermore, gate hysteresis is partially attributed to carrier injection from SWNT to environmental dielectrics such as moisture. Therefore, removal of moisture surrounding SWNT in vacuum and low temperature condition leads to reduction in gate hysteresis.